2015
DOI: 10.15420/ecr.2015.10.01.31
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is a hereditary primary myocardial disease that is most commonly due to mutations within genes encoding sarcomeric contractile proteins and is characterised by left ventricular hypertrophy in the absence of a cardiac or systemic cause. Although the overall prognosis is relatively good with an annual mortality rate <1 %, the propensity to potentially fatal ventricular arrhythmias is the most feared complication. The identification of patients at risk of arrhythmogenic sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…Nevertheless, some evidence suggests it might be a useful marker for sudden death as it is correlated to an increased risk of fatal arrhythmias [17]. Currently, there are no official recommendations for the use of highresolution electrocardiography in the risk stratification of HCM patients [18]. Since these shreds of evidence are controversial, we aimed to investigate the association between late potentials and familial sudden death, syncope, and complex ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some evidence suggests it might be a useful marker for sudden death as it is correlated to an increased risk of fatal arrhythmias [17]. Currently, there are no official recommendations for the use of highresolution electrocardiography in the risk stratification of HCM patients [18]. Since these shreds of evidence are controversial, we aimed to investigate the association between late potentials and familial sudden death, syncope, and complex ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…However, in HCM patients, the indications for the implant remain unclear. Primary and secondary sudden death prevention in HCM patients is supported by the European Society of Cardiology Guidelines, especially in patients with a familial history of HCM, unexplained syncope, severe left ventricular hypertrophy, non-sustained tachycardia and history of aborted sudden death [18][19]. Maron et al demonstrated that the implant was effective in 11% of patients as secondary prevention and 5% as primary prevention in high-risk HCM subjects [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other risk modifiers that are considered are: (1) late-gadolinium enhancement (LGE) on cardiac MRIs [69], (2) double mutations with compound heterozygotes and digenic carriers [70], (3) marked LVOT obstruction (Gradient ≥ 30 mmHg), and (4) LV apical aneurysms with LGE [71].…”
Section: Prevention Of Scdmentioning
confidence: 99%
“…Heterogeneous delayed enhanced compatibility with fibrosis was detected in the middle myocardium of the inferior and superior segments of the septal wall. The risk of sudden death was 2.68% using the HCM Risk-SCD calculator, which did not recommended ICD implantation 2,4 . He was recommended to completely stop physical exercise.…”
Section: Case Descriptionmentioning
confidence: 99%